THREE PAPERS IN ARABIC ON THE HISTORY OF THE NORTH MUHAJIRUN IN THE EASTERN DIVISION OF THE NATIONAL LIBRARY. CYRIL AND METHODIUS (SOFIA, BULGARIA) - Navruzov, Amir Ramazanovic; Bobrovnikov, Vladimir Olegovic (History, Archeology and Ethnography of the Caucasus, 2009)
In the East section of the Public library. Cyril and Methodius (Sofia, Bulgaria) in the funds 315a and 315ar "Russia" are stored documents in Turkish and Arabic on the history of the North Caucasian muhajirism. Russian and foreign Orientalists in the period of 1960-1980 noted the existence of this curious collection, allowing a new look at the history of the border regions of the Ottoman and Russian empires for many centuries XVII-XVIII at the end of the XIX century Вноябре2008 in the Eastern Department of the Public library. Cyril and Methodius (people's library "St. St. Cyril and methods) in Sofia (Bulgaria) worked expedition Of the Institute of Oriental studies from Moscow. It included the employee of Institute Vladimir Olegovich Bobrovnikov (the head of an expedition) and two Orientalists from Makhachkala– known in the North Caucasus Turkologist Hasan Magomedrasulovich Orazayev and Arabist Amir Ramazanovich Navruzov.The aim of the work was to identify and collect the most characteristic and important documents on the history of Muslim emigration (muhajirism) from the Russian pre-revolutionary Caucasus to the Balkans and other regions of the Ottoman Empire, the cultural ties of the border regions of both empires and the formation of the so-called Circassian Diaspora in the Middle East of the late XIX-XX centuries. The initiated study is truly revolutionary for domestic Caucasian studies. Until now, the history of the Exodus of the Muslims of the Caucasus after the end of the protracted war of 1817-1864 was written exclusively on the materials of Russian archives.
Keywords: Public library of Cyril and Methodius; Bulgaria; Caucasus; Muhajirs of the Caucasus; letters; Fund "Russia".